IL-36α induces maturation of Th1-inducing human MDDC and synergises with IFN-γ to induce high surface expression of CD14 and CD11c - Higgins, John; Mutamba, Shilla; Mahida, Yashwant R.; Barrow, Paul; Foster, Neil (Elsevier, 2015)
We show that IL-36α induced maturation of human MDDCs and stimulated differentiation of IFN-γ producing (Type 1) CD3+ lymphocytes but was not as effective as IL-36β in doing so. For the first time, we also show that IL-36α induced expression of CD14 by MDDCs and this was highly potentiated by co-cultured with IFN-γ. In contrast, lipopolysaccharide (LPS) did not increase CD14 expression by MDDCs, suggesting that if MDDCs represent a physiologically relevant population in vivo, they need to be stimulated by relevant inflammatory cytokines prior to CD14 expression and detection of LPS, expressed by Gram negative bacteria. IFN-γ synergised with IL-36α to restore the high levels of CD11c expression by MDDCs, which was reduced by culture with these cytokines in isolation. IL-36α/IFN-γ synergy also correlated with increased binding of the opsonic complement protein (iC3b) to MDDCs. However although IL-36α increased the phagocytic capacity of MDDCs for Salmonella Typhimurium 4/74 this was not synergistically increased by IFN-γ (P > 0.05).